The predominance of the neoliberal agenda in the contemporary world: hegemony and consequences - Pineda Nebot, Carmen; Fonseca, Francisco (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
Thirty years ago the world economy, especially the developed countries, suffered, as it is the case now, a severe economic crisis. That situation arose a new regulatory model of capitalist economies is called neo-liberalism. Since then, with more or less force, has been present in all countries, taking advantage of these conditions to constantly repeat the same principles: the reduction of the State, the advantages of the market and self-regulation of this, etc. Although its premises seem simple or simple neo-liberalism is a complex and changing project whose political and economic sustainability constantly reinvents itself and whose governance and spatiality is necessary to observe and analyze whether you want to advance in viable alternatives. Neo-liberalism does not live away from alternative projects but is mixed with the alternatives, has a form of governance that mutates, which changes. With this communication we seek to know something more about the similarities and differences that this ideology presents of the countries
Keywords: liberalism; keynesianism; neoliberalism; ultraliberalism